An LC–MS/MS method for steroid profiling during adrenal venous sampling for investigation of primary aldosteronism. Issue 145 (January 2015) - Peitzsch, Mirko; Dekkers, Tanja; Haase, Matthias; Sweep, Fred C.G.J.; Quack, Ivo; Antoch, Gerald; Siegert, Gabriele; Lenders, Jacques W.M.; Deinum, Jaap; Willenberg, Holger S.; Eisenhofer, Graeme
Highlights: LC–MS/MS based quantification of 15 steroids in peripheral and adrenal venous samples. Sensitivity sufficient for reliable aldosterone measurements in peripheral plasma. Utility for clinical work-up of primary aldosteronism due to included hybrid steroids. AV/pV step-ups for most other steroids higher than for cortisol. Cosyntropin stimulation during AVS changes relative adrenal secretion of steroid. Abstract: Background: Steroid profiling for diagnosis of endocrine disorders featuring disordered production of steroid hormones is now possible from advances in liquid chromatography with tandem mass spectrometry (LC–MS/MS). Adrenal venous (AV) measurements of aldosterone and cortisol are a standard practice in the clinical work-up of primary aldosteronism, but do not yet take advantage of steroid profiling. Methods: A novel LC–MS/MS based method was developed for simultaneous measurement of 15 adrenal steroids: aldosterone, corticosterone, 11-deoxycorticosterone, progesterone, pregnenolone, cortisone, cortisol, 11-deoxycortisol, 17-hydroxyprogesterone, androstenedione, dehydroepiandrosterone, dehydroepiandrosterone-sulfate, 21-deoxycortisol, 18-oxocortisol and 18-hydroxycortisol. These were compared in peripheral venous (pV) and AV plasma from 70 patients undergoing AV sampling with and without cosyntropin stimulation. Aldosterone and cortisol levels measured by LC–MS/MS were compared with those measured by immunoassay. Results: Reproducibility of measurements with coefficients of variation ≤10% as well as analytical sensitivity sufficient to measure low pV levels particularly of aldosterone demonstrate the utility of the assay for profiling adrenal steroids in primary aldosteronism. Method comparisons indicated assay and concentration dependent differences of cortisol and aldosterone concentrations measured by immunoassay and LC–MS/MS. Median AV/pV ratios of 11-deoxycortisol (53.0), 17-hydroxyprogesterone (33.4), pregnenolone (62.4), androstenedione (40.6) and dehydroepiandrosterone (33.3) were 2.9- to, 5.4-fold larger than those for cortisol (11.6), with additionally generally larger increases than for cortisol with than without cosyntropin stimulation. Conclusion: Our LC–MS/MS assay, in addition to improvements over existing immunoassay measurements of aldosterone and cortisol, offers profiling of 13 other adrenal steroids, providing a potentially useful method for the clinical work-up of patients with primary aldosteronism. In particular, the larger AV/pV ratios of several steroids compared to cortisol suggest more sensitive alternatives to the latter for assessing positioning of AV sampling catheters.